Changes in soil biogeochemistry following disturbance by girdling and mountain pine beetles in subalpine forests - Trahan, Nicole A.; Dynes, Emily L.; Pugh, Evan; Moore, David J. P.; Monson, Russell K. (Oecologia, 2015)
A recent unprecedented epidemic of beetleinduced tree mortality has occurred in the lodgepole pine forests of Western North America. Here, we present the results of studies in two subalpine forests in the Rocky Mountains, one that experienced natural pine beetle disturbance and one that experienced simulated disturbance imposed through bole girdling. We assessed changes to soil microclimate and biogeochemical pools in plots representing different post-disturbance chronosequences. High plot tree mortality, whether due to girdling or beetle infestation, caused similar alterations in soil nutrient pools. During the first 4 years after disturbance, sharp declines were observed in the soil dissolved organic carbon (DOC) concentration (45-51 %), microbial biomass carbon concentration (33-39 %), dissolved organic nitrogen (DON) concentration (31-42 %), and inorganic phosphorus (PO₄³⁻) concentration (53-55 %). Five to six years after disturbance, concentrations of DOC, DON, and PO₄³⁻ recovered to 71-140 % of those measured in undisturbed plots. Recovery was coincident with observed increases in litter depth and the sublitter, soil O-horizon. During the 4 years following disturbance, soil ammonium, but not nitrate, increased to 2-3 times the levels measured in undisturbed plots. Microbial biomass N increased in plots where increased ammonium was available. Our results show that previously observed declines in soil respiration following beetle-induced disturbance are accompanied by losses in key soil nutrients. Recovery of the soil nutrient pool occurs only after several years following disturbance, and is correlated with progressive mineralization of dead tree litter.